METODOLOGI TEOLOGI AL ASY’ARY DAN PENGARUHNYA TERHADAP PENDIDIKAN ISLAM DI INDONESIA - Muchasan, Ali; Syarif, M; Naufal, Mochammad (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2023)
The Indonesian understanding of Ahlus Sunnah Islam rests on the understanding of Asyariyah theology which is the basis for building the religious beliefs of the majority of Indonesian Muslims. This understanding of kalam or theology that was taught by Imam Ash'ari has given birth to a methodology of thinking that has a strong influence on various fields of Islamic religion, especially in the field of education. Al Asy'ari's moderate thinking style in translating the core teachings of Islam has influenced how traditional Islamic education in Indonesia takes an elastic and moderate form in responding to various social religious religious issues that are developing in Indonesia. Al Asyari's moderate style of thinking in time will also influence the development of educational institutions in Indonesia, especially madrasas which seek to eclecticly combine the Islamic scientific approach which is